2009
DOI: 10.1111/j.1551-2916.2009.03394.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Electrical Properties of Lead‐Free Perovskite Ba(Al1/2Nb1/2)O3

Abstract: Lead-free perovskite Ba(Al 1/2 Nb 1/2 )O 3 was prepared by conventional ceramic fabrication technique at 13501C/5 h in air atmosphere. The crystal symmetry, space group and unit cell dimensions were determined from the experimental results using FullProf software whereas crystallite size and lattice strain were estimated from Williamson-Hall approach. X-ray diffraction analysis of the compound indicated the formation of a singlephase monoclinic structure with the space group P2/m. EDAX and SEM studies were car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Thus, the observed dielectric dispersion at low frequency may be due to the polarization mechanism associated with the thermally activated conduction of mobile ions and/or other defects. Similar behavior has been reported by Kamal et al [37] on the sample of Ba(Al 1/2 Nb 1/2 )O 3 . …”
Section: Complex Permittivity Representationsupporting
confidence: 75%
“…Thus, the observed dielectric dispersion at low frequency may be due to the polarization mechanism associated with the thermally activated conduction of mobile ions and/or other defects. Similar behavior has been reported by Kamal et al [37] on the sample of Ba(Al 1/2 Nb 1/2 )O 3 . …”
Section: Complex Permittivity Representationsupporting
confidence: 75%
“…The low value of lattice strain might be due to the fact that the synthesis procedure (through thermochemical reaction) does not impose much constraint in the formation of compound as is generally found in case of extensive ball milling technique, strained layer growth, etc. [9,10].…”
Section: Resultsmentioning
confidence: 97%
“…The real and imaginary parts of permittivity were obtained from the impedance data in a conventional way using the following relations [9,21]:…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years much attention has been paid to the development of lead free ceramic having either comparable or superior electrical properties than its lead containing counterparts. This is due to the fact that lead containing materials has been restricted for making devices by the EU since Jan. 2004 due to the toxicity of lead oxide, which causes environment pollution during its waste disposal (Prasad et al 2010). The electrical properties of a number of solid-solutions of Ba(Fe1/2Ta1/2)O3 (Li et al 2004), Ba(Fe1/2Nb1/2)O3 (Bhagat et al 2014;Yang et al 2012;Singh et al 2012;Intatha et al 2011), Ba(Sm1/2Nb1/2)O3 (AmarNath and Prasad 2012), Ba(Bi1/2Ta1/2)O3 (Kumar et al 2014), Ba(Y1/2Nb1/2)O3 , with BaTiO3 have been reported recently.…”
Section: Introductionmentioning
confidence: 99%